2014
DOI: 10.2139/ssrn.2428039
|View full text |Cite
|
Sign up to set email alerts
|

Budget Deficit, Money Growth and Inflation: Empirical Evidence from Vietnam

Abstract: This study empirically examines the nexus among budget deficit, money supply and inflation by using a monthly data set from January 1995 to December 2012 and a SVAR model with five endogenous variables, inflation, money growth, budget deficit growth, real GDP growth and interest rate. Since real GDP and budget deficit are unavailable on the monthly basis, we interpolate those series using Chow and Lin's (1971) annualized approach from their annual series. Overall, we found that money growth has positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Tekin- Koru and Özmen (2003) found that monetary growth had a positive impact while budget deficit had a no effect on inflation in the case of Turkish. The findings of Tekin-Koru and Özmen ( 2003) were similar with Khieu (2014) in Vietnem and Mukhtar and Zakaria (2010) in Pakistan. By investigating the granger causality effects of these two policies on inflation, Lozano-Espitia ( 2008) discovered that budget deficit granger cause monetary growth and subsequently, monetary growth to cause inflation in Colombia.…”
Section: Empirical Evidence On the Relationship Between The Monetary Policy Fiscal Policy And Inflationmentioning
confidence: 54%
“…Tekin- Koru and Özmen (2003) found that monetary growth had a positive impact while budget deficit had a no effect on inflation in the case of Turkish. The findings of Tekin-Koru and Özmen ( 2003) were similar with Khieu (2014) in Vietnem and Mukhtar and Zakaria (2010) in Pakistan. By investigating the granger causality effects of these two policies on inflation, Lozano-Espitia ( 2008) discovered that budget deficit granger cause monetary growth and subsequently, monetary growth to cause inflation in Colombia.…”
Section: Empirical Evidence On the Relationship Between The Monetary Policy Fiscal Policy And Inflationmentioning
confidence: 54%
“…Specifically, inflation should rise for three months regarding a positive shock to money growth. Besides, the second month from the shock is the time when the positive shock to the money supply has the strongest effect on inflation (Khieu, 2014). Nguyen (2015) affirms that most studies prove the strong effect of monetary support on inflation.…”
Section: Literature Reviewmentioning
confidence: 61%
“…Money supply has been shown to be a vital factor that increased inflation with data from January 2001 to February 2009 in Vietnam (Nguyen et al, 2012). Also, in Vietnam, Khieu (2014) proves that monetary growth positively affects the inflation rate. Specifically, inflation should rise for three months regarding a positive shock to money growth.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…The empirical results show an overall increase in public expenditure causes an increase in the rate of unemployment. Khieu (2014) investigates the relationship between budget deficit, money supply, and inflation.…”
Section: Literature Reviewmentioning
confidence: 99%